Preparation process of halogenated butyl rubber for improving high temperature resistance of tire

Through the modified nanofiller and gradient vulcanization design, the problem of limited thermal conductivity and weak interface combination in the halogenated butyl rubber formula is solved, and an efficient thermal conductivity network and dual cross-linking network are realized, which improves the high temperature resistance and service life of the tire.

CN120424448APending Publication Date: 2025-08-05SHANDONG YOUYOU RUBBER TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510409632.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-02
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

In the traditional halogenated butyl rubber formula, nanofillers are prone to agglomeration, limited thermal conductivity, high dynamic heat generation, weak interface bonding, poor oxygen resistance effect, and difficult to effectively delay thermal oxygen degradation.

Method used

Premodification treatment of nano-alumina and silane coupling agent Si69 is adopted, combined with the segmented temperature control process in the refining stage to form an efficient thermal conductivity network; modified montmorillonite is combined with carbon black N660 to inhibit oxygen permeation by using the sheet barrier effect; the free radical capture ability of nano-cerium oxide CeO2 is combined with the gradient vulcanization design of microencapsulated sulfur and peroxide DCP to construct a dual crosslinking network where C-C bonds and C-S bonds coexist.

Benefits of technology

It significantly improves the high temperature resistance of halogenated butyl rubber, reduces dynamic heat generation by 20%, increases the tensile strength retention rate to 90%, reduces permanent deformation of high-temperature compression by 35%, extends the service life of the tire, improves processing safety and tear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120424448A_ABST
    Figure CN120424448A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of halogenated butyl rubber for improving high temperature resistance of a tire. According to the invention, the high temperature resistance is obviously improved through multi-scale filler cooperation and interface strengthening. The pre-modification treatment of nano aluminum oxide and a silane coupling agent Si69 is combined with a segmented temperature control process in an internal mixing stage, so that nano particles are uniformly dispersed in a rubber matrix, an efficient heat-conducting network is formed, and the dynamic heat generation is reduced by 20% or above; a compound filling system of a modified montmorillonite organic intercalation and carbon black N660 inhibits oxygen permeation by using a lamellar barrier effect, and is matched with the free radical capture capability of nano cerium oxide CeO2, so that the tensile strength retention rate of the rubber material is increased to 90% after the rubber material is thermally aged for 96 hours at the high temperature of 150 DEG C. Meanwhile, due to the gradient vulcanization design of the microencapsulated sulfur and the dicumyl peroxide DCP, a C-C bond and C-S bond coexisting dual cross-linked network is constructed in the dynamic vulcanization stage, the high-temperature compression permanent deformation is reduced by 35%, and the service life of the tire under the extreme working condition is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tire rubber, and specifically relates to a preparation process of halogenated butyl rubber for improving the high-temperature resistance of tires. Background Art

[0002] Halogenated butyl rubber for tires is a synthetic rubber with excellent airtightness, heat resistance, and aging resistance. It is primarily modified by introducing halogen atoms (such as chlorine or bromine) into the butyl rubber molecule. Halogenated butyl rubber is primarily used in tire manufacturing as a sealant for inner tubes and tire sidewalls. Its excellent chemical stability effectively prevents gas permeation and maintains tire pressure, thereby improving driving safety and fuel economy. Halogenated butyl rubber also enhances tire durability and wet-skid resistance, making it suitable for a variety of complex road conditions. Due to its exceptional performance, halogenated butyl rubber is increasingly used in the tire industry, playing a significant role in improving overall tire performance and market competitiveness.

[0003] However, in traditional halogenated butyl rubber formulas, nanofillers are prone to agglomeration due to the lack of surface modification and rough mixing process, resulting in limited thermal conductivity, high dynamic heat generation, and aggravated thermal aging inside the tire; at the same time, when carbon black and montmorillonite are compounded, the interface bonding is weak and the oxygen barrier effect is poor, making it difficult to effectively delay thermal oxidative degradation. Summary of the Invention

[0004] The purpose of the present invention is to provide a preparation process of halogenated butyl rubber for improving the high temperature resistance of tires in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: a preparation process of halogenated butyl rubber for improving the high temperature resistance of tires, characterized in that the preparation process comprises the following steps:

[0006] S1: Weigh the raw materials first, weighing: 100-120 parts by weight of brominated butyl rubber, 15-20 parts by weight of nano-alumina, 40-50 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, 3 parts by weight of nano-cerium oxide CeO2, 2-5 parts by weight of high molecular weight antioxidant PBN, 1.5-2 parts by weight of microencapsulated sulfur, 1.2-3.0 parts by weight of dicumyl peroxide DCP, 3-10 parts by weight of active zinc oxide, 1 part by weight of stearic acid, 5 parts by weight of polyethylene glycol PEG-4000, 2 parts by weight of zinc borate, and 1.5 parts by weight of silane coupling agent Si69;

[0007] Bromobutyl rubber BIIR 2030 was preheated in an oven at 60°C for 2 hours, and 30 nm nano-alumina and silane coupling agent Si69 were premixed in proportion and dry-mixed in a high-speed mixer for 5 minutes.

[0008] S2: The preheated bromobutyl rubber was placed in an internal mixer, and stearic acid, zinc oxide active agent, polyethylene glycol PEG-4000 and zinc borate were added in sequence, and the mixture was mixed for 3 minutes; then carbon black N660, modified montmorillonite organic intercalation and pretreated nano-alumina mixture were added in two batches, the mixer speed was 70 rpm, the temperature was raised to 110°C, and the mixture was mixed for 8 minutes;

[0009] S3: Transfer the masterbatch to an open mill, add nano cerium oxide CeO2 and high molecular weight antioxidant PBN, and pass it through the mill three times;

[0010] S4: The rubber mixture was placed in a constant temperature room at 25°C for 12 hours;

[0011] S5: The static rubber compound was put back into the internal mixer, microencapsulated sulfur and dicumyl peroxide DCP were added, and the mixture was mixed at a low speed of 40 rpm for 4 minutes;

[0012] S6: A two-stage mixing process was used: the first stage was shearing at 120°C for 3 minutes, and the second stage was heated to 140°C and the pressure was 12 MPa for 5 minutes;

[0013] S7: The rubber material is rolled into a 2 mm thick film by a four-roll calender, bubbles are removed by ultrasonic vibration, and the film is cooled to room temperature;

[0014] S8: On the open mill, the film is thinly passed 3 times to make a rubber blank to be vulcanized with a thickness of 1.5 mm;

[0015] S9: The rubber blank is loaded into the mold, and the first stage vulcanization is performed at 160°C for 15 minutes, and the second stage vulcanization is performed at 180°C for 2 hours. After that, the preparation process of the halogenated butyl rubber for improving the high temperature resistance of the tire is completed.

[0016] In a preferred embodiment, in step S1, bromobutyl rubber BIIR 2030 is continuously preheated in a constant temperature oven at 60° C. for 2 hours to remove moisture adsorbed on the surface of the raw material and improve its fluidity; at the same time, nano-alumina 30 nm and silane coupling agent Si69 are weighed according to a weight ratio and then put into a high-speed blender and dry-mixed at a speed of 1000 rpm for 5 minutes to uniformly coat the surface of the nano-alumina with the silane coupling agent to form a modified nano-filler premix.

[0017] In a preferred embodiment, in step S2, the preheated bromobutyl rubber is put into an internal mixer, the initial temperature is set to 80°C, and 1 part by weight of stearic acid, 3 parts by weight of active zinc oxide, 5 parts by weight of polyethylene glycol PEG-4000, and 2 parts by weight of zinc borate are added in sequence, and the mixture is mixed for 3 minutes to disperse the basic additives; then 40 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, and 15 parts by weight of pretreated nano-alumina-Si69 mixture are added in two portions, the mixer speed is adjusted to 70 rpm, the temperature is gradually increased to 110°C during mixing, and mixing is continued for 8 minutes until the torque curve stabilizes to form a uniform masterbatch.

[0018] In a preferred embodiment, in step S3, the masterbatch is transferred to a two-roll mill, the roller temperature is set to 50°C, the roller distance is adjusted to 0.5 mm, 3 parts by weight of nano-cerium oxide CeO2 and 2 parts by weight of high molecular weight antioxidant PBN are added in batches, and the masterbatch is continuously thinned three times to force the nano-cerium oxide and antioxidant to fully penetrate into the rubber phase by utilizing the shear force of the rollers until no visible particles are aggregated on the surface of the rubber compound.

[0019] In a preferred embodiment, in step S4, the mixed masterbatch is spread in a constant temperature and humidity chamber, the ambient temperature is controlled to be 25° C. and the relative humidity is ≤30%, and it is left to stand for 12 hours to achieve sufficient interfacial bonding between the filler and the rubber molecular chain through physical adsorption and chemical bonding, thereby eliminating the internal stress generated during the mixing process.

[0020] In a preferred embodiment, in step S5, the rubber material after standing is put back into the internal mixer, the internal mixer chamber temperature is set to no more than 80° C., 1.5 parts by weight of microencapsulated sulfur and 1.2 parts by weight of dicumyl peroxide (DCP) are slowly added at a low speed of 40 rpm, and the rubber material is immediately discharged after mixing for 4 minutes to avoid premature release or decomposition of the vulcanizing agent due to shear heat.

[0021] In a preferred embodiment, in step S6, a two-stage internal mixing process is adopted: in the first stage, the temperature is set at 120° C. and the rotation speed is 50 rpm in the internal mixer, and shear mixing is continued for 3 minutes to cause the microencapsulated sulfur shell to rupture and slowly release the active sulfur; in the second stage, the temperature is increased to 140° C., and a pressure of 12 MPa is applied and maintained for 5 minutes. The free radicals generated by the decomposition of DCP at high temperature initiate covalent crosslinking between rubber molecular chains, thereby forming a more heat-resistant coexisting network of CC bonds and CS bonds.

[0022] In a preferred embodiment, in step S7, the dynamically vulcanized rubber material is conveyed to a four-roll calender, the temperatures of the upper and middle rollers are set to 70°C, and the temperature of the lower roller is set to 65°C. The roller gap is adjusted to calender a continuous film with a thickness of 2.0±0.1 mm. At the same time, the ultrasonic generator is turned on to apply high-frequency vibration of 28 kHz for 30 seconds to eliminate residual bubbles in the rubber material, and then the film is wound and naturally cooled at room temperature.

[0023] In a preferred embodiment, in step S8, the cooled rubber sheet is placed on an open mill, the roller temperature is set to 40°C, the roller distance is gradually reduced to 0.3 mm, and three thin-pass operations are performed. After each thin-pass, the rubber sheet is folded and the feeding direction is adjusted, and finally a rubber blank to be vulcanized with a uniform thickness of 1.5±0.1 mm and a smooth and defect-free surface is obtained.

[0024] In a preferred embodiment, in step S9, the rubber blank is cut and loaded into a flat vulcanization mold preheated to 160°C. First, a first-stage vulcanization is performed: a constant temperature of 160°C is maintained at a pressure of 8 MPa for 15 minutes to complete the main cross-linking reaction; then the vulcanized rubber is transferred to a circulating hot air oven for a second-stage vulcanization, with a set temperature of 180°C and a heat treatment at normal pressure for 2 hours to further eliminate residual stress and strengthen the high-temperature resistant cross-linked network structure.

[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0026] 1. In the present invention, high-temperature resistance is significantly improved through the synergy of multi-scale fillers and interface reinforcement. The pre-modification treatment of nano-alumina and silane coupling agent Si69, combined with the segmented temperature control process in the mixing stage, achieves uniform dispersion of nanoparticles in the rubber matrix, forming an efficient thermal conductivity network and reducing dynamic heat generation by more than 20%. The composite filling system of modified montmorillonite organic intercalation and carbon black N660 utilizes the layer barrier effect to inhibit oxygen permeation. Combined with the free radical capture ability of nano-cerium oxide CeO2, the tensile strength retention rate of the rubber compound is increased to 90% after 96 hours of thermal aging at 150°C. At the same time, the gradient vulcanization design of microencapsulated sulfur and diisopropylbenzene peroxide (DCP) constructs a dual cross-linked network with coexistence of CC and CS bonds during the dynamic vulcanization stage (120°C → 140°C), reducing high-temperature compression set by 35%, significantly extending the service life of the tire under extreme working conditions.

[0027] 2. In this invention, a staged mixing strategy combined with ultrasonic-assisted calendering effectively prevents nanofiller agglomeration and premature activation of the vulcanizer, extending the rubber's Mooney scorch time to over 25 minutes and improving processing safety. A two-stage vulcanization process strengthens the heat-resistant network through a post-crosslinking reaction, raising the rubber's glass transition temperature to -35°C while maintaining a hardness range of 70±5 Shore A, balancing flexibility and high-temperature rigidity. The resulting halogenated butyl rubber product exhibits a reduced dynamic fatigue crack growth rate at high temperatures, further enhancing overall tear resistance and making the tire more durable. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the process principle of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] Example 1:

[0031] Reference Figure 1 A process for preparing halogenated butyl rubber for improving the high temperature resistance of tires, the process comprising the following steps:

[0032] S1: Weigh the raw materials first, weighing: 100 parts by weight of brominated butyl rubber, 15 parts by weight of nano-alumina, 40 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, 3 parts by weight of nano-cerium oxide CeO2, 2 parts by weight of high molecular weight antioxidant PBN, 1.5 parts by weight of microencapsulated sulfur, 1.2 parts by weight of dicumyl peroxide DCP, 3 parts by weight of active zinc oxide, 1 part by weight of stearic acid, 5 parts by weight of polyethylene glycol PEG-4000, 2 parts by weight of zinc borate, and 1.5 parts by weight of silane coupling agent Si69;

[0033] Bromobutyl rubber BIIR 2030 was preheated in an oven at 60°C for 2 hours, and 30 nm nano-alumina and silane coupling agent Si69 were premixed in proportion and dry-mixed in a high-speed mixer for 5 minutes.

[0034] S2: The preheated bromobutyl rubber was placed in an internal mixer, and stearic acid, zinc oxide active agent, polyethylene glycol PEG-4000 and zinc borate were added in sequence, and the mixture was mixed for 3 minutes; then carbon black N660, modified montmorillonite organic intercalation and pretreated nano-alumina mixture were added in two batches, the mixer speed was 70 rpm, the temperature was raised to 110°C, and the mixture was mixed for 8 minutes;

[0035] S3: Transfer the masterbatch to an open mill, add nano cerium oxide CeO2 and high molecular weight antioxidant PBN, and pass through the mill three times;

[0036] S4: The rubber mixture was placed in a constant temperature room at 25°C for 12 hours;

[0037] S5: The static rubber compound was put back into the internal mixer, microencapsulated sulfur and dicumyl peroxide DCP were added, and the mixture was mixed at a low speed of 40 rpm for 4 minutes;

[0038] S6: A two-stage mixing process was used: the first stage was shearing at 120°C for 3 minutes, and the second stage was heated to 140°C and the pressure was 12 MPa for 5 minutes;

[0039] S7: The rubber material is rolled into a 2 mm thick film by a four-roll calender, bubbles are removed by ultrasonic vibration, and the film is cooled to room temperature;

[0040] S8: On the open mill, the film is thinly passed 3 times to make a rubber blank to be vulcanized with a thickness of 1.5 mm;

[0041] S9: The rubber blank is loaded into the mold, and the first stage vulcanization is performed at 160°C for 15 minutes, and the second stage vulcanization is performed at 180°C for 2 hours. After that, the preparation process of the halogenated butyl rubber for improving the high temperature resistance of the tire is completed.

[0042] In step S1, bromobutyl rubber BIIR 2030 is continuously preheated in a constant temperature oven at 60° C. for 2 hours to remove moisture adsorbed on the surface of the raw material and improve its fluidity. Simultaneously, 30 nm nano-alumina and silane coupling agent Si69 are weighed according to a weight ratio and then added to a high-speed blender. The mixture is dry-mixed at a speed of 1000 rpm for 5 minutes to uniformly coat the surface of the nano-alumina with the silane coupling agent, thereby forming a modified nanofiller premix.

[0043] In step S2, the preheated bromobutyl rubber is put into an internal mixer, the initial temperature is set to 80° C., and 1 part by weight of stearic acid, 3 parts by weight of active zinc oxide, 5 parts by weight of polyethylene glycol PEG-4000, and 2 parts by weight of zinc borate are added in sequence, and the mixture is mixed for 3 minutes to disperse the basic additives; then, 40 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, and 15 parts by weight of a pretreated nano-alumina-Si69 mixture are added in two portions, the mixer speed is adjusted to 70 rpm, the temperature is gradually increased to 110° C. during mixing, and mixing is continued for 8 minutes until the torque curve stabilizes to form a uniform masterbatch.

[0044] In step S3, the masterbatch is transferred to a two-roll mill, the roller temperature is set to 50° C., the roller distance is adjusted to 0.5 mm, 3 parts by weight of nano-cerium oxide CeO2 and 2 parts by weight of a high molecular weight antioxidant PBN are added in batches, and the masterbatch is continuously thinned three times to force the nano-cerium oxide and the antioxidant to fully penetrate into the rubber phase by utilizing the shear force of the rollers until no visible particles are aggregated on the surface of the rubber compound.

[0045] In step S4, the mixed masterbatch is spread in a constant temperature and humidity chamber, the ambient temperature is controlled to be 25° C. and the relative humidity is ≤30%, and it is left to stand for 12 hours to achieve sufficient interface bonding between the filler and the rubber molecular chain through physical adsorption and chemical bonding, thereby eliminating the internal stress generated during the mixing process.

[0046] In step S5, the rubber material after standing is put back into the internal mixer, the internal mixer chamber temperature is set to no more than 80° C., and 1.5 parts by weight of microencapsulated sulfur and 1.2 parts by weight of dicumyl peroxide (DCP) are slowly added at a low speed of 40 rpm. After mixing for 4 minutes, the rubber material is immediately discharged to avoid premature release or decomposition of the vulcanizing agent due to shear heat generation.

[0047] In step S6, a two-stage internal mixing process is adopted: in the first stage, the temperature is set at 120° C. and the rotation speed is 50 rpm in the internal mixer, and shear mixing is continued for 3 minutes to cause the microencapsulated sulfur shell to rupture and slowly release the active sulfur; in the second stage, the temperature is increased to 140° C., and a pressure of 12 MPa is applied and maintained for 5 minutes. The free radicals generated by the decomposition of DCP at high temperature trigger covalent crosslinking between rubber molecular chains, forming a more heat-resistant coexisting network of C—C bonds and C—S bonds.

[0048] In step S7, the dynamically vulcanized rubber material is conveyed to a four-roll calender, the temperatures of the upper and middle rollers are set to 70°C, and the temperature of the lower roller is set to 65°C. The roller gap is adjusted to calender a continuous film with a thickness of 2.0±0.1 mm. At the same time, the ultrasonic generator is turned on to apply high-frequency vibration of 28 kHz for 30 seconds to eliminate residual bubbles in the rubber material, and then the film is wound and naturally cooled at room temperature.

[0049] In step S8, the cooled rubber sheet is placed on an open mixing mill, the roller temperature is set to 40° C., the roller distance is gradually reduced to 0.3 mm, and three thin-pass operations are performed. After each thin-pass, the rubber sheet is folded and the feeding direction is adjusted, and finally a rubber blank to be vulcanized with a uniform thickness of 1.5±0.1 mm and a smooth surface without defects is obtained.

[0050] In step S9, the rubber blank is cut and loaded into a flat vulcanization mold preheated to 160° C., and first undergoes a first-stage vulcanization process: maintaining a constant temperature of 160° C. under a pressure of 8 MPa for 15 minutes to complete the primary cross-linking reaction; then, the vulcanized rubber is transferred to a circulating hot air oven for a second-stage vulcanization process, with a set temperature of 180° C. and a heat treatment at normal pressure for 2 hours to further eliminate residual stress and strengthen the high-temperature resistant cross-linked network structure.

[0051] From the above, it can be seen that the present invention significantly improves high-temperature resistance through the synergy of multi-scale fillers and interface reinforcement. The pre-modification treatment of nano-alumina and silane coupling agent Si69, combined with the segmented temperature control process in the mixing stage, achieves uniform dispersion of nanoparticles in the rubber matrix, forming an efficient thermal conductivity network and reducing dynamic heat generation by more than 20%. The composite filling system of modified montmorillonite organic intercalation and carbon black N660 utilizes the layer barrier effect to inhibit oxygen permeation. Combined with the free radical capture ability of nano-cerium oxide CeO2, the tensile strength retention rate of the rubber compound is increased to 90% after 96 hours of thermal aging at 150°C. At the same time, the gradient vulcanization design of microencapsulated sulfur and diisopropylbenzene peroxide (DCP) constructs a dual cross-linked network with coexistence of CC bonds and CS bonds during the dynamic vulcanization stage (120°C→140°C), reducing high-temperature compression set by 35%, significantly extending the service life of the tire under extreme working conditions.

[0052] In this invention, a staged mixing strategy combined with ultrasonic-assisted calendering effectively prevents nanofiller agglomeration and premature activation of the vulcanizer, extending the Mooney scorch time of the rubber compound to over 25 minutes and improving processing safety. A two-stage vulcanization process strengthens the heat-resistant network through a post-crosslinking reaction, raising the rubber's glass transition temperature to -35°C while maintaining a hardness within the range of 70±5 Shore A, achieving a balance between flexibility and high-temperature rigidity. The resulting halogenated butyl rubber product exhibits a reduced dynamic fatigue crack growth rate at high temperatures, further improving overall tear resistance and making the tire more durable.

[0053] Example 2:

[0054] Reference Figure 1 A process for preparing halogenated butyl rubber for improving the high temperature resistance of tires, the process comprising the following steps:

[0055] S1: Weigh the raw materials first, weighing: 1120 parts by weight of brominated butyl rubber, 20 parts by weight of nano-alumina, 50 parts by weight of carbon black N660, 3 parts by weight of modified montmorillonite organic intercalation, 5 parts by weight of nano-cerium oxide CeO2, 5 parts by weight of high molecular weight antioxidant PBN, 2 parts by weight of microencapsulated sulfur, 3.0 parts by weight of dicumyl peroxide DCP, 10 parts by weight of active zinc oxide, 1 part by weight of stearic acid, 5 parts by weight of polyethylene glycol PEG-4000, 2 parts by weight of zinc borate, and 1.5 parts by weight of silane coupling agent Si69;

[0056] Bromobutyl rubber BIIR 2030 was preheated in an oven at 60°C for 2 hours, and 30 nm nano-alumina and silane coupling agent Si69 were premixed in proportion and dry-mixed in a high-speed mixer for 5 minutes.

[0057] S2: The preheated bromobutyl rubber was placed in an internal mixer, and stearic acid, zinc oxide active agent, polyethylene glycol PEG-4000 and zinc borate were added in sequence, and the mixture was mixed for 3 minutes; then carbon black N660, modified montmorillonite organic intercalation and pretreated nano-alumina mixture were added in two batches, the mixer speed was 70 rpm, the temperature was raised to 110°C, and the mixture was mixed for 8 minutes;

[0058] S3: Transfer the masterbatch to an open mill, add nano cerium oxide CeO2 and high molecular weight antioxidant PBN, and pass through the mill three times;

[0059] S4: The rubber mixture was placed in a constant temperature room at 25°C for 12 hours;

[0060] S5: The static rubber compound was put back into the internal mixer, microencapsulated sulfur and dicumyl peroxide DCP were added, and the mixture was mixed at a low speed of 40 rpm for 4 minutes;

[0061] S6: A two-stage mixing process was used: the first stage was shearing at 120°C for 3 minutes, and the second stage was heated to 140°C and the pressure was 12 MPa for 5 minutes;

[0062] S7: The rubber material is rolled into a 2 mm thick film by a four-roll calender, bubbles are removed by ultrasonic vibration, and the film is cooled to room temperature;

[0063] S8: On the open mill, the film is thinly passed 3 times to make a rubber blank to be vulcanized with a thickness of 1.5 mm;

[0064] S9: The rubber blank is loaded into the mold, and the first stage vulcanization is performed at 160°C for 15 minutes, and the second stage vulcanization is performed at 180°C for 2 hours. After that, the preparation process of the halogenated butyl rubber for improving the high temperature resistance of the tire is completed.

[0065] In step S1, bromobutyl rubber BIIR 2030 is continuously preheated in a constant temperature oven at 60° C. for 2 hours to remove moisture adsorbed on the surface of the raw material and improve its fluidity. Simultaneously, 30 nm nano-alumina and silane coupling agent Si69 are weighed according to a weight ratio and then added to a high-speed blender. The mixture is dry-mixed at a speed of 1000 rpm for 5 minutes to uniformly coat the surface of the nano-alumina with the silane coupling agent, thereby forming a modified nanofiller premix.

[0066] In step S2, the preheated bromobutyl rubber is put into an internal mixer, the initial temperature is set to 80° C., and 1 part by weight of stearic acid, 3 parts by weight of active zinc oxide, 5 parts by weight of polyethylene glycol PEG-4000, and 2 parts by weight of zinc borate are added in sequence, and the mixture is mixed for 3 minutes to disperse the basic additives; then, 40 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, and 15 parts by weight of a pretreated nano-alumina-Si69 mixture are added in two portions, the mixer speed is adjusted to 70 rpm, the temperature is gradually increased to 110° C. during mixing, and mixing is continued for 8 minutes until the torque curve stabilizes to form a uniform masterbatch.

[0067] In step S3, the masterbatch is transferred to a two-roll mill, the roller temperature is set to 50° C., the roller distance is adjusted to 0.5 mm, 3 parts by weight of nano-cerium oxide CeO2 and 2 parts by weight of a high molecular weight antioxidant PBN are added in batches, and the masterbatch is continuously thinned three times to force the nano-cerium oxide and the antioxidant to fully penetrate into the rubber phase by utilizing the shear force of the rollers until no visible particles are aggregated on the surface of the rubber compound.

[0068] In step S4, the mixed masterbatch is spread in a constant temperature and humidity chamber, the ambient temperature is controlled to be 25° C. and the relative humidity is ≤30%, and it is left to stand for 12 hours to achieve sufficient interface bonding between the filler and the rubber molecular chain through physical adsorption and chemical bonding, thereby eliminating the internal stress generated during the mixing process.

[0069] In step S5, the rubber material after standing is put back into the internal mixer, the internal mixer chamber temperature is set to no more than 80° C., and 1.5 parts by weight of microencapsulated sulfur and 1.2 parts by weight of dicumyl peroxide (DCP) are slowly added at a low speed of 40 rpm. After mixing for 4 minutes, the rubber material is immediately discharged to avoid premature release or decomposition of the vulcanizing agent due to shear heat generation.

[0070] In step S6, a two-stage internal mixing process is adopted: in the first stage, the temperature is set at 120° C. and the rotation speed is 50 rpm in the internal mixer, and shear mixing is continued for 3 minutes to cause the microencapsulated sulfur shell to rupture and slowly release the active sulfur; in the second stage, the temperature is increased to 140° C., and a pressure of 12 MPa is applied and maintained for 5 minutes. The free radicals generated by the decomposition of DCP at high temperature trigger covalent crosslinking between rubber molecular chains, forming a more heat-resistant coexisting network of C—C bonds and C—S bonds.

[0071] In step S7, the dynamically vulcanized rubber material is conveyed to a four-roll calender, the temperatures of the upper and middle rollers are set to 70°C, and the temperature of the lower roller is set to 65°C. The roller gap is adjusted to calender a continuous film with a thickness of 2.0±0.1 mm. At the same time, the ultrasonic generator is turned on to apply high-frequency vibration of 28 kHz for 30 seconds to eliminate residual bubbles in the rubber material, and then the film is wound and naturally cooled at room temperature.

[0072] In step S8, the cooled rubber sheet is placed on an open mixing mill, the roller temperature is set to 40° C., the roller distance is gradually reduced to 0.3 mm, and three thin-pass operations are performed. After each thin-pass, the rubber sheet is folded and the feeding direction is adjusted, and finally a rubber blank to be vulcanized with a uniform thickness of 1.5±0.1 mm and a smooth surface without defects is obtained.

[0073] In step S9, the rubber blank is cut and loaded into a flat vulcanization mold preheated to 160° C., and first undergoes a first-stage vulcanization process: maintaining a constant temperature of 160° C. under a pressure of 8 MPa for 15 minutes to complete the primary cross-linking reaction; then, the vulcanized rubber is transferred to a circulating hot air oven for a second-stage vulcanization process, with a set temperature of 180° C. and a heat treatment at normal pressure for 2 hours to further eliminate residual stress and strengthen the high-temperature resistant cross-linked network structure.

[0074] From the above, it can be seen that the present invention significantly improves high-temperature resistance through the synergy of multi-scale fillers and interface reinforcement. The pre-modification treatment of nano-alumina and silane coupling agent Si69, combined with the segmented temperature control process in the mixing stage, achieves uniform dispersion of nanoparticles in the rubber matrix, forming an efficient thermal conductivity network and reducing dynamic heat generation by more than 20%. The composite filling system of modified montmorillonite organic intercalation and carbon black N660 utilizes the layer barrier effect to inhibit oxygen permeation. Combined with the free radical capture ability of nano-cerium oxide CeO2, the tensile strength retention rate of the rubber compound is increased to 90% after 96 hours of thermal aging at 150°C. At the same time, the gradient vulcanization design of microencapsulated sulfur and diisopropylbenzene peroxide (DCP) constructs a dual cross-linked network with coexistence of CC bonds and CS bonds during the dynamic vulcanization stage (120°C→140°C), reducing high-temperature compression set by 35%, significantly extending the service life of the tire under extreme working conditions.

[0075] In this invention, a staged mixing strategy combined with ultrasonic-assisted calendering effectively prevents nanofiller agglomeration and premature activation of the vulcanizer, extending the Mooney scorch time of the rubber compound to over 25 minutes and improving processing safety. A two-stage vulcanization process strengthens the heat-resistant network through a post-crosslinking reaction, raising the rubber's glass transition temperature to -35°C while maintaining a hardness within the range of 70±5 Shore A, achieving a balance between flexibility and high-temperature rigidity. The resulting halogenated butyl rubber product exhibits a reduced dynamic fatigue crack growth rate at high temperatures, further improving overall tear resistance and making the tire more durable.

[0076] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply the existence of any such actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article, or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or device. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, article, or device comprising the element.

[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A process for preparing halogenated butyl rubber for improving the high temperature resistance of tires, characterized by: The preparation process comprises the following steps: S1: Weigh the raw materials first, weighing: 100-120 parts by weight of brominated butyl rubber, 15-20 parts by weight of nano-alumina, 40-50 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, 3 parts by weight of nano-cerium oxide CeO2, 2-5 parts by weight of high molecular weight antioxidant PBN, 1.5-2 parts by weight of microencapsulated sulfur, 1.2-3.0 parts by weight of dicumyl peroxide DCP, 3-10 parts by weight of active zinc oxide, 1 part by weight of stearic acid, 5 parts by weight of polyethylene glycol PEG-4000, 2 parts by weight of zinc borate, and 1.5 parts by weight of silane coupling agent Si69; Bromobutyl rubber BIIR 2030 was preheated in an oven at 60°C for 2 hours, and 30 nm nano-alumina and silane coupling agent Si69 were premixed in proportion and dry-mixed in a high-speed mixer for 5 minutes. S2: The preheated bromobutyl rubber was placed in an internal mixer, and stearic acid, zinc oxide active agent, polyethylene glycol PEG-4000 and zinc borate were added in sequence, and the mixture was mixed for 3 minutes; then carbon black N660, modified montmorillonite organic intercalation and pretreated nano-alumina mixture were added in two batches, the mixer speed was 70 rpm, the temperature was raised to 110°C, and the mixture was mixed for 8 minutes; S3: Transfer the masterbatch to an open mill, add nano cerium oxide CeO2 and high molecular weight antioxidant PBN, and pass it through the mill three times; S4: The rubber mixture was placed in a constant temperature room at 25°C for 12 hours; S5: The static rubber compound was put back into the internal mixer, microencapsulated sulfur and dicumyl peroxide DCP were added, and the mixture was mixed at a low speed of 40 rpm for 4 minutes; S6: A two-stage mixing process was used: the first stage was shearing at 120°C for 3 minutes, and the second stage was heated to 140°C and the pressure was 12 MPa for 5 minutes; S7: The rubber material is rolled into a 2 mm thick film by a four-roll calender, bubbles are removed by ultrasonic vibration, and the film is cooled to room temperature; S8: On the open mill, the film is thinly passed 3 times to make a rubber blank to be vulcanized with a thickness of 1.5 mm; S9: The rubber blank is loaded into the mold, and the first stage vulcanization is performed at 160°C for 15 minutes, and the second stage vulcanization is performed at 180°C for 2 hours. After that, the preparation process of the halogenated butyl rubber for improving the high temperature resistance of the tire is completed.

2. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S1, bromobutyl rubber BIIR 2030 is continuously preheated in a constant temperature oven at 60° C. for 2 hours to remove moisture adsorbed on the surface of the raw material and improve its fluidity. Simultaneously, 30 nm nano-alumina and silane coupling agent Si69 are weighed according to a weight ratio and then added to a high-speed blender. The mixture is dry-mixed at a speed of 1000 rpm for 5 minutes to uniformly coat the surface of the nano-alumina with the silane coupling agent, thereby forming a modified nanofiller premix.

3. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S2, the preheated bromobutyl rubber is put into an internal mixer, the initial temperature is set to 80° C., and 1 part by weight of stearic acid, 3 parts by weight of active zinc oxide, 5 parts by weight of polyethylene glycol PEG-4000, and 2 parts by weight of zinc borate are added in sequence, and the mixture is mixed for 3 minutes to disperse the basic additives; then, 40 parts by weight of carbon black N660, 5 parts by weight of modified montmorillonite organic intercalation, and 15 parts by weight of a pretreated nano-alumina-Si69 mixture are added in two portions, the mixer speed is adjusted to 70 rpm, the temperature is gradually increased to 110° C. during mixing, and mixing is continued for 8 minutes until the torque curve stabilizes to form a uniform masterbatch.

4. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S3, the masterbatch is transferred to a two-roll mill, the roller temperature is set to 50° C., the roller distance is adjusted to 0.5 mm, 3 parts by weight of nano-cerium oxide CeO2 and 2 parts by weight of a high molecular weight antioxidant PBN are added in batches, and the masterbatch is continuously thinned three times to force the nano-cerium oxide and the antioxidant to fully penetrate into the rubber phase by utilizing the shear force of the rollers until no visible particles are aggregated on the surface of the rubber compound.

5. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S4, the mixed masterbatch is spread in a constant temperature and humidity chamber, the ambient temperature is controlled to be 25° C. and the relative humidity is ≤30%, and it is left to stand for 12 hours to achieve sufficient interface bonding between the filler and the rubber molecular chain through physical adsorption and chemical bonding, thereby eliminating the internal stress generated during the mixing process.

6. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S5, the rubber material after standing is put back into the internal mixer, the internal mixer chamber temperature is set to no more than 80° C., and 1.5 parts by weight of microencapsulated sulfur and 1.2 parts by weight of dicumyl peroxide (DCP) are slowly added at a low speed of 40 rpm. After mixing for 4 minutes, the rubber material is immediately discharged to avoid premature release or decomposition of the vulcanizing agent due to shear heat generation.

7. The process for preparing halogenated butyl rubber for improving high temperature resistance of tires according to claim 1, wherein: In step S6, a two-stage internal mixing process is adopted: in the first stage, the temperature is set at 120° C. and the rotation speed is 50 rpm in the internal mixer, and shear mixing is continued for 3 minutes to cause the microencapsulated sulfur shell to rupture and slowly release the active sulfur; in the second stage, the temperature is increased to 140° C., and a pressure of 12 MPa is applied and maintained for 5 minutes. The free radicals generated by the decomposition of DCP at high temperature trigger covalent crosslinking between rubber molecular chains, forming a more heat-resistant coexisting network of C—C bonds and C—S bonds.

8. The process for preparing halogenated butyl rubber for improving the high temperature resistance of tires according to claim 1, wherein: In step S7, the dynamically vulcanized rubber material is conveyed to a four-roll calender, the temperatures of the upper and middle rollers are set to 70°C, and the temperature of the lower roller is set to 65°C. The roller gap is adjusted to calender a continuous film with a thickness of 2.0±0.1 mm. At the same time, the ultrasonic generator is turned on to apply high-frequency vibration of 28 kHz for 30 seconds to eliminate residual bubbles in the rubber material, and then the film is wound and naturally cooled at room temperature.

9. The process for preparing halogenated butyl rubber for improving high temperature resistance of tires according to claim 1, wherein: In step S8, the cooled rubber sheet is placed on an open mixing mill, the roller temperature is set to 40° C., the roller distance is gradually reduced to 0.3 mm, and three thin-pass operations are performed. After each thin-pass, the rubber sheet is folded and the feeding direction is adjusted, and finally a rubber blank to be vulcanized with a uniform thickness of 1.5±0.1 mm and a smooth surface without defects is obtained.

10. The process for preparing halogenated butyl rubber for improving high temperature resistance of tires according to claim 1, characterized in that: In step S9, the rubber blank is cut and loaded into a flat vulcanization mold preheated to 160° C., and first undergoes a first-stage vulcanization process: maintaining a constant temperature of 160° C. under a pressure of 8 MPa for 15 minutes to complete the primary cross-linking reaction; then, the vulcanized rubber is transferred to a circulating hot air oven for a second-stage vulcanization process, with a set temperature of 180° C. and a heat treatment at normal pressure for 2 hours to further eliminate residual stress and strengthen the high-temperature resistant cross-linked network structure.

Citation Information

Cited By

  • Preparation method of high-temperature-resistant and anti-aging butyl rubber

    CN121249062A